The correlation between Growth Mindset and Score of English Language Proficiency Test in the English Department of UNP - Melisa Putri; Senorica Yulia Sari (Journal of English Language Teaching, 2023)
This study aims to determine the correlation between growth mindset and English proficiency scores, such as TOEFL, IELTS, English score, duolinggo, and others. This research is a correlation study using a quantitative approach. This study used a questionnaire as a research instrument. The questionnaire consists of 15 statements with 6 alternative answers related to growth mindset. The number of respondents in this study were 50 students from the English Department at UNP who were selected using purposive sampling method. Based on the results of the study, it was found that the level of students' growth mindset was at a high level, the majority of students' English proficiency scores were at the A2 (Elementary level) and B1 (Intermediate level) levels, the correlation coefficient value was 0.030 which was greater than 0.05. So it can be concluded that there is a positive correlation between growth mindset and English proficiency scores with the correlation coefficient being at a weak level of correlation.